The Development of a Virtual Laboratory Based on Problems in the Circulatory System Matter - Yulia Ramdinawati Syam; Rita Retnowati; Surti Kurniasih (Postgraduate, University of Mataram, 2023)
Practicum in biology learning is an important element that allows students to observe, try, and test scientific concepts directly. However, the problems faced such as limited equipment, costs and time are obstacles. Therefore, the use of a virtual laboratory is needed to overcome this problem. This research aims to develop a problem-based virtual laboratory on circulatory system material. This virtual laboratory not only presents practical simulations that are close to reality but also challenges in the form of problems related to blood circulation that students need to solve. The laboratory was developed with a menu containing competencies, materials, practicums, and evaluations. The research method used was Research and Development (R&D) with the ADDIE model. The instrument was a questionnaire for 20 Biology teachers, expert lecturers, and students. The results showed the validity results of media and material experts of 94% and a VCR value of 0.969 which means valid so that it can be concluded that the development of problem-based virtual laboratories on circulatory system material is suitable for use as a medium in the learning process in High School